Transport and Secretion of the Wnt3 Ligand by Motor Neuron-like Cells and Developing Motor Neurons - Cristina Pinto; Viviana Pérez; Jessica Mella; Miguel Albistur; Teresa Caprile; Francisca C. Bronfman; Juan Pablo Henríquez (Biomolecules, 2021)
The vertebrate neuromuscular junction (NMJ) is formed by a presynaptic motor nerve terminal and a postsynaptic muscle specialization. Cumulative evidence reveals that Wnt ligands secreted by the nerve terminal control crucial steps of NMJ synaptogenesis. For instance, the Wnt3 ligand is expressed by motor neurons at the time of NMJ formation and induces postsynaptic differentiation in recently formed muscle fibers. However, the behavior of presynaptic-derived Wnt ligands at the vertebrate NMJ has not been deeply analyzed. Here, we conducted overexpression experiments to study the expression, distribution, secretion, and function of Wnt3 by transfection of the motor neuron-like NSC-34 cell line and by in ovo electroporation of chick motor neurons. Our findings reveal that Wnt3 is transported along motor axons in vivo following a vesicular-like pattern and reaches the NMJ area. In vitro, we found that endogenous Wnt3 expression increases as the differentiation of NSC-34 cells proceeds. Although NSC-34 cells overexpressing Wnt3 do not modify their morphological differentiation towards a neuronal phenotype, they effectively induce acetylcholine receptor clustering on co-cultured myotubes. These findings support the notion that presynaptic Wnt3 is transported and secreted by motor neurons to induce postsynaptic differentiation in nascent NMJs.